1968
DOI: 10.1002/ijc.2910030120
|View full text |Cite
|
Sign up to set email alerts
|

Possible association between pernicious anaemia and leukaemia: A prospective study of 1,625 patients with a note on the very high incidence of stomach cancer

Abstract: Several patients with pernicious anaemia have been reported to have developed leukaemia and the suggestion has been made that the two diseases are aetiologically associated.Sixteen hundred and twenty-five patients attending eight pernicious anaemia clinics were, therefore, followed from the time of their first attendance to I January, 1964 In most of the patients who developed both diseases the Ieukaemia was of the myeloid type ( I 5 out of a total of 21 reportedpreviously or in this series).In 1957, Blackbur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
2
1

Year Published

1971
1971
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 2 publications
3
16
2
1
Order By: Relevance
“…In this cohort study of patients with PA we found a two-fold increase in the risk for stomach cancer in accordance with previous estimates (Blackburn et al, 1968;Brinton et al, 1989;Hsing et al, 1993). Our finding of an excess of cancer of the buccal cavity and pharynx is consistent with findings in the two large US and Swedish studies (Brinton et al, 1989;Hsing et al, 1993).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this cohort study of patients with PA we found a two-fold increase in the risk for stomach cancer in accordance with previous estimates (Blackburn et al, 1968;Brinton et al, 1989;Hsing et al, 1993). Our finding of an excess of cancer of the buccal cavity and pharynx is consistent with findings in the two large US and Swedish studies (Brinton et al, 1989;Hsing et al, 1993).…”
Section: Discussionsupporting
confidence: 92%
“…Several previous studies have documented an increased incidence of stomach cancer in patients with pernicious anaemia (PA) (Blackburn et al, 1968;Elsborg and Mosbech, 1979;Borch et al, 1988;Brinton et al, 1989;Hsing et al, 1993). An increase in the risk for other upper gastrointestinal cancers such as buccal cavity and pharynx (Brinton et al, 1989;Hsing et al, 1993) and oesophagus (Hsing et al, 1993) has also been reported, as well as increases for other digestive organ cancers [liver, biliary tract and pancreas (Hsing et al, 1993)], though these cancers have been investigated less extensively among PA patients than stomach cancer.…”
mentioning
confidence: 99%
“…Although the 2.1% prevalence of pernicious anaemia among 917 gastric cancer patients was not significantly higher than that of 1.4% among age-matched controls, the difference was significant when analysis was restricted to patients diagnosed with pernicious anaemia more than 5 years before cancer diagnosis. In addition, a follow-up study of 1,625 pernicious anaemia patients (Blackburn et al, 1968) found that, after excluding deaths in early periods when selective inclusion of patients may have occurred, the 29 deaths from stomach cancer significantly exceeded the 7.3 deaths expected, resulting in a SIR of 4.0 -a figure only slightly higher than the risk of 3.2 found in the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…In addition, when examined as a group, the risk of oral and pharyngeal cancers increased with the interval since diagnosis of pernicious anaemia, reaching a significant risk of 2-fold with 6 or more years of latency. The major risk factors for oral and pharyngeal cancers are smoking and drinking (Blot et al, 1988). However, since the risks for lung cancer were low in our survey (SIR=0.8), it appeared that smoking may be less prevalent than in the general population.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation